1981
DOI: 10.2514/3.57789
|View full text |Cite
|
Sign up to set email alerts
|

Design, Analysis, and Tests of a Shuttle-Type Heat-Pipe-Cooled Leading Edge

Abstract: A one-half-scale heat-pipe-cooled leading edge model was designed and fabricated to verify feasibility and performance of a full-scale Shuttle-type orbiter design. Model performance was investigated experimentally by radiant heating and aerothermal tests and analytically by using a simple technique which predicts heat pipe startup from the frozen state and also predicts transient and steady-state thermal behavior. Analytical results agree well with experimental results for startup and steady-state heat pipe op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…by heating fuel). Several heat pipe concepts have been explored [33], [34], [35], [36], including the development of a heat pipe leading edge for the Space Shuttle Orbiter [33]. ________________________________________________________________________ Because passive concepts suffer from both excessive mass (case 1) and low fracture toughness (case 2), and the added complexity of an active concept is not desirable, we limit further discussion here to the passive concepts of cases 3 to 5; namely ablative, hot structure, and heat pipe TPS, which are most suited for the thermo-mechanical stress state at a hypersonic vehicle's leading edges.…”
Section: The Tps Conceptmentioning
confidence: 99%
See 3 more Smart Citations
“…by heating fuel). Several heat pipe concepts have been explored [33], [34], [35], [36], including the development of a heat pipe leading edge for the Space Shuttle Orbiter [33]. ________________________________________________________________________ Because passive concepts suffer from both excessive mass (case 1) and low fracture toughness (case 2), and the added complexity of an active concept is not desirable, we limit further discussion here to the passive concepts of cases 3 to 5; namely ablative, hot structure, and heat pipe TPS, which are most suited for the thermo-mechanical stress state at a hypersonic vehicle's leading edges.…”
Section: The Tps Conceptmentioning
confidence: 99%
“…The concept of coupling heat pipes to leading edges has received only limited investigation [34], [35], [36], [75], [76]. Nearly all leading edge heat pipe concepts employed arrays of hollow circular tubes or channels either metallurgically joined to a high temperature skin or embedded in a wedge-shaped composite [33], [34], [35], [36].…”
Section: Figure 211 Cross-section Schematic Of a Cylindrical Heat Pmentioning
confidence: 99%
See 2 more Smart Citations
“…4). This model was tested by a series of radiant heat and aerothermal tests at NASA LaRC from 1977 to 1978 to verify heat-pipe transient, startup, and steady-state performance [12][13][14]. In 1979, to optimize a heat-pipecooled wing leading edge for a single-stage-to-orbit vehicle, Peeples's [15] study indicated that the mass of a shuttle-type heat-pipe-cooled leading edge could be reduced by over 40 % by use of a more efficient structural design.…”
Section: Heat-balance Thermal Protections With High Thermal Conductivmentioning
confidence: 99%